Bi-Functional Extension on Heterogeneous ORR/OER Catalysis with 2D Materials for Li-O2 Batteries - Zhang, Guoliang; Yu, Han; Yang, Ruonan; Fan, Yuqi; Wang, Ning; Guo, Zhanhu; Dang, Feng (Nano-Micro Letters, 2026)
In the integration of heterogeneous catalysis with two-dimensional (2D) materials, Li–O2 batteries serve as valuable research prototypes, particularly for investigating the efficient oxygen reduction/evolution reaction in multiphase environments. However, the advantages and limitations associated with the unique anisotropy and electronic properties of 2D materials in Li–O2 batteries (LOBs) remain unclear. This Review provides a comprehensive overview of 2D cathode catalysts for LOBs, including graphene, transition metal oxides/hydroxides, dichalcogenides, and metal carbides, together with their corresponding activation engineering strategies. More specifically, we thoroughly examine the pivotal role of anisotropic catalytic properties on the large surface areas and terminal edge active sites of 2D cathode catalysts. The correlations are analyzed between 2D material design and catalytic mechanisms in LOBs, particularly in adsorption strength of intermediates, electronic structure and discharge product. Additionally, the expanded applications of 2D materials in components such as lithium anode protection and rapid lithium-ion transport are also briefly discussed by leveraging their favorable physicochemical properties. Finally, the challenges and future directions for the development and application of 2D materials are summarized and discussed, which is expected to unlock the full potential of LOBs batteries as next-generation energy storage technologies. Highlights: 1 This review systematically summarizes the catalytic performance of two-dimensional (2D) materials in Li–O2 batteries, together with activation strategies spanning point, line, plane, and bulk dimensions. 2 The catalytic mechanisms and key descriptors of 2D materials are analyzed, including the adsorption strength of intermediates, electronic structure, and product evolution. 3 The multifunctional roles of 2D materials in Li–O2 batteries are discussed, including separators, electrolyte additives, and lithium anode protection.